"Conversion" of epistatic into additive genetic variance in finite populations and possible impact on long‐term selection response1. (June 2017) - Hill, W.G.
Summary: The role of epistasis in understanding the genetic architecture and variation of quantitative traits and its role, if any, in artificial selection and livestock improvement more generally has a long and sometimes controversial history. Its presence has been clearly demonstrated in, for example, laboratory experiments, but the amount of variation it contributes is likely to be small in outbred populations. In a finite population, although additive x additive epistatic variance is lost by genetic drift, it also contributes by conversion to additive variance through drift sampling and therefore has a potential indirect role in medium and long‐term selection response, with superficial similarity to and hard to distinguish from mutation. Whilst predictions of response require knowledge of genetic parameters, an infinitesimal model provides some analytic results. Otherwise there is little quantitative information relevant to animal populations on which to judge this potential role of epistasis and reach firm conclusions.